Biden's Security Policy: Democratic Security or Democratic Exceptionalism? - Simona R. Soare (Intereconomics, 2021)
By emphasising the internal-external security nexus inherent in democratic security, the US could aspire again to lead through the example of its democracy's resilience and ability to self-correct.
Keywords: 330; Außenpolitik; Nationale Sicherheit; USA